AM228 students perception on lecturer personality traits at UiTM Malacca City Campus / Mohammed Ammar Abu Bakar - Abu Bakar, Mohammed Ammar (Faculty of Administrative Science and Policy Studies, 2014)
The study seeks to determine the possible factors that can influence students perception towards their lecturer. A sample of 101 out of 316 student’s at UiTM Malacca City Campus had been selected for this study. The findings also showed that the independent variables or factors that support our hypothesis are extraversion, agreeableness, neuroticism, openness to experience and conscientiousness, in which all of these variables have significant correlation with the dependent variable which is students perception towards their lecturer.